Ninth Five Year Plan 1997-2002 Volume-VII Government of Assam - Planning Commission (Planning Commission, 1997)
The economy of the two Hill districts of Assam depends mainly on Agriculture. Almost 90% of the population are engaged in Agriculture, Therefore to bring about significant development of the hill districts planned development of Agriculture deserves prime consideration. SITUATION - The Hill region of Assam comprises two districts mainly Karbi Anglong and N.C. Hills with a total geographical area of 15,222 Sq. K.M. which is about 15.4% of the state. The zone is located in between 25° and 26.41° North1 latitude and 92.32° and 93.53° east longitude. The top ogre of these two hill districts varies from plain to steep slopes.
Development Commissioner for Hill Areas